Detecting and Defending against Replication Attacks in Wireless Sensor Networks - Xiang-yi Chen; Li-xia Meng; Yong-zhao Zhan (International Journal of Distributed Sensor Networks)
Wireless sensor networks are susceptible to node replication attacks due to their unattended nature. Existing replicas detection schemes can be further improved in regard of detection probabilities, detection overheads, and the balance of detection overheads among sensor nodes. In this paper, we make the following contributions: first, we point out the unrealistic assumption that the replica node would behave honestly as the benign sensor nodes; thus the existing detection schemes would fail if the replica nodes cheat or collude with the compromised node. Then, we propose a location-binding symmetric key scheme forcing the replica nodes to be inserted only in the vicinity of the compromised node. Later, a detecting scheme is presented to inspect the location claims within the neighborhood. Finally, analysis shows that our scheme helps to detect and defend against replication attacks effectively and efficiently. Extensive simulations are conducted and the results show that the detection overheads are low and evenly distributed among all the sensor nodes.